PROFIL GERMANIUM SEGIEMPAT PADA TRANSISTOR BIPOLAR SILIKON-GERMANIUM - Julian, Engeline Shintadewi (Jurnal Teknik Elektro, 2002)
This paper presents a study of the effect of different starting edges position in the base ofSi/SiGe/Si HBTs. The germanium profile in the base under study is rectangular. In thesimulations, the effect of band gap narrowing due to heavy doping and band gap narrowingdue to the addition of germanium in the base of the HBT are included. The simulations aredone with BIPOLE3. The results show that the starting edge positions have strong influence inthe current gain and maximum transit frequency of the HBTsKeywords: SiGe, HBT, band gap narrowing, Bipole 3.